Periodontal characteristics of diabetic patients with tooth mobility - Ojehanon, Patrick I; Azodo, Clement C; Erhabor, Paul; Orhue, Vera (Journal of Social Health and Diabetes, 2017)
Objective: To determine the periodontal characteristics of diabetic patients with tooth mobility attending the Periodontology Clinic of University of Benin Teaching Hospital (UBTH), Benin City, Nigeria.Materials and Methods: This cross-sectional observational study was conducted among diabetic patients with tooth mobility in the Periodontology Clinic in UBTH, Benin City, Nigeria. The indices recorded for the participants were gingival index, community periodontal index of treatment need, and Miller'sindex for tooth mobility.Results: A total of 54 participants who met the inclusion criteria were approached, but only 49 of them consented and participated in this study giving a 90.7% recruitment rate. The age range and mean age of the participants were 42–84 years and 63.84 ± 1.31 years, respectively. The self-reported age of diagnosis was between 41 and 70 years with a mean age of 56.22 ± 6.88 years. About two-thirds (67.3%) of the participants were males. Less than half (38.8%) of patients were visiting the dentist for the first time. Mandibular arch housed about two-thirds (64.9%) of the mobile teeth and mandibular left quadrant housed about one-third of (34.5%) the mobile teeth. Central incisor (42.3%) constituted the most mobile teeth followed by the first molar (28.9%). A total of 17.0% of the mobile teeth were Miller's Grade 3 mobility. More than one-third (28.5%) (code 3 = 26.5%, code 4 = 2.0%) of the participants had periodontal pockets. More than half (52.7%) of participants had probing pocket depth of 5 mm and above. The gingival score which had mean as 1.60 ± 0.08 was significantly associated with age of the participants. The mean probing depth was 4.86 ± 0.21 mm. The probing depth was significant with age and duration of diabetes mellitus (DM) of the participants.Conclusion: Data from this study revealed that age of diagnosis of diabetes with tooth mobility was higher than previously reported. The most mobile teeth and earliest teeth to become mobile were the mandibular incisors, and Grade 1 severity constituted the majority. DM with tooth mobility exhibited gingival score and probing depth that had a variable significant association with demographic characteristics.
Keywords: Dentition; diabetes mellitus; periodontal diseases; tooth mobility